EVALUATION OF IN VITRO ANTIBACTERIAL ACTIVITY AND MEDIAN LETHAL DOSE ESTIMATION OF A SIDDHA POLYHERBAL FORMULATION: SINGINATHA CHOORNAM IN RAT MODEL - V.GEETHA; S.ELANSEKARAN; V.THANIGAVELAN; V.KALIYAMURTHI; P.PARTHIBAN; K.KANAGAVALLI (International Journal of Pharma and Bio Sciences, 2015)
Singinatha Choornam, a Siddha polyherbal formulation has been prescribed for Allergic Rhinosinusitis in the literature. The objective was to evaluate the antibacterial activity and safety of Singinatha Choornam in a rat model. Initially, Physico chemical characterization studies were done adopting a methodology of Pharmacopoeial Laboratory for Indian Medicine. Antibacterial study was done by Kirby-Bauer disc diffusion method against gram positive and negative strains comparing with Ciprofloxacin. An Acute toxicity study was done on female wistar albino rat under OECD guidelines 423. Physicochemical parameters results can be used as standard in future for maintaining quality of this drug. Staphylococcus aureus and Escherchia coli were susceptible to 50 µl/disc of aqueous extract of the test drug prepared with 5 g of sample in 50 ml of distilled water. Acute oral toxicity study of Singinatha Choornam revealed no mortality even at the dosage of 2000 mg/kg body weight justifies its recommended therapeutic dosage of 1 g.